Genome‐wide identification of blood DNA methylation patterns associated with early‐onset hepatocellular carcinoma development in hepatitis B carriers. Issue 2 (10th June 2016) - Kao, Wei‐Yi; Yang, Shu‐Han; Liu, Wen‐Jie; Yeh, Meng‐Yin; Lin, Chih‐Lin; Liu, Chun‐Jen; Huang, Chi‐Jung; Lin, Shi‐Ming; Lee, Shou‐Dong; Chen, Pei‐Jer; Yu, Ming‐Whei
Abstract : The etiology of early‐onset hepatocellular carcinoma (HCC) among hepatitis B virus (HBV) carriers remains unclear. DNA methylation levels in peripheral leukocytes have been associated with different environmental exposures and immune or inflammatory response. We aimed to identify methylation signatures of peripheral leukocytes that could track hepatitis B progression to HCC, especially for early‐onset HCC. We first performed an epigenome‐wide association analysis on 48 matched case‐control pairs in a nested case‐control study within a 22‐yr follow‐up cohort of HBV carriers. Through this analysis we found that progression to early‐onset HCC involved methylation variable positions across the genome, in which a substantial proportion displayed significant variation due to HBV viral load, chronic hepatitis status, and/or leukocyte subtype composition, and these associations were significantly enriched among genes in immune pathways. Methylation at probes cg00300879, cg06872964, and cg07080864, that are located within the proximal promoter of CNKSR1, IFI44L, and PENK, respectively, was validated by bisulfite pyrosequencing and findings were replicated in a case‐sibling study of early‐onset HCC (134 cases vs. 174 sibling controls). Furthermore, a high methylation score, constructed using the three probes, was predictive for the risk of early‐onset HCC in two datasets (adjusted‐odds ratios = 0.21–0.32, P ≤ 0.0206). This association was also observed for late‐onset HCC (adjusted‐odds ratio = 0.42–0.47, P ≤ 0.0194) in a nested case‐control study (120 cases vs. 178 controls). In prospective analysis, change in the score was detected 5–9 yr before HCC onset. Blood‐based methylation profiling provides new insights into the complexity of virus‐host interaction underlying HBV‐related HCC, holding promise for the disease risk management. © 2016 Wiley Periodicals, Inc.